The Financial Implications of Carbon Transparency: Examining the Mediating Role of Emission Disclosure - Dewi, Catur Kumala; Aprilia, Juwita; Indrawati, Andi (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: The purpose of this research is to examine the relationship between carbon emissions disclosure as an intervening variable between corporate governance, capital expenditures, and financial performance. Method: Companies listed on the Indonesia Stock Exchange (IDX) that are involved in manufacturing are the primary focus of the study. The research employs a purposive sampling technique to select 16 organizations, resulting in 80 data observations spanning the period from 2019 to 2023. The correlations among variables are examined using path analysis, which is conducted with IBM SPSS Statistics 26. Findings: Gender diversity on boards has a favorable effect on a company's bottom line, according to the study's results. The business's financial performance is negatively affected by the size of the audit committee. Carbon emissions disclosure, on the other hand, is unaffected by factors like board size, gender diversity, or audit committee size. Capital spending, board size, and disclosure of carbon emissions do not substantially affect the financial success of firms. Carbon emissions disclosure also does not mediate the relationship between boards' size, gender diversity, capital spending, audit committee size, and business financial performance. Novelty/Value: This study provides insights into the limited role of carbon emissions disclosure as a mediator in corporate financial performance, highlighting the complex interactions between governance factors and sustainability reporting, especially on carbon emission disclosure.